Trading in Influence: Modus Baru dalam Korupsi Indonesia Tahun 2022 dan Paradoks Kriminalisasi : Trading in Influence: Indonesia's New Mode of Corruption in 2022 and the Criminalization Paradox - Djamil, Nasrullah (JAAMTER : Jurnal Audit Akuntansi Manajemen Terintegrasi, 2023)
This study evaluates the handling of corruption cases by the Prosecutor's Office, the Police and the Corruption Eradication Commission throughout 2022 and gives a fair grade (C) with a handling percentage of about 50% of the target of 2,772 cases. A comparative assessment of the last five years illustrates the dynamics of the handling of corruption cases. Quantitative charts highlight trends in enforcement, from the number of cases to potential losses to the state. Mapping corruption cases using the influence peddling mode involves identifying, analyzing, and summarizing patterns. Mapping steps include identification of cases, analysis of characteristics, creation of visual maps, integration of contextual factors, trend analysis, and recommendations. This mapping supports the understanding and formulation of strategies for dealing with corruption cases using the influence trading mode. In 2022, budget abuse dominates, followed by price gouging and fictitious activities. The high prevalence of these three methods indicates a lack of oversight in development and widespread corruption in the procurement of goods and services. Of the 579 cases, 43% involved the procurement of goods and services. Influence trading methods were also identified and used 19 times. The delegation of great authority to regional heads creates bargaining in the promotion and transfer of ASN. The case of buying and selling positions involving Regional Heads and ASN reflects the symbiosis between the two, with greed for power and ASN's desire to obtain immediate positions. The rise in this case is likened to an iceberg phenomenon, with the possibility that many cases have yet to be discovered.